Teacher’s Directives Speech Acts in Teaching-Learning Interactions: Classroom Discourse Analysis (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
Students' responses to the teacher's directive speech act are often not in line with expectations becaused they do not pay attention to the social context, interactional context and individual agency. The objectives of this research are: to describe the social context dimensions, the interactional context dimensions, and the individual agency onteacher’s directive speech act in teaching – learning interactions. This research uses a qualitative description approach and theoretical approach to classroom discourse analysis (Rymes). There is a variety of social distance (familiarity), teacher's high social status, interaction formalities situation, and the dominance of affective and referential functions in teacher's directive speech acts. Teacher's directive speech acts bring predictable, unpredictable interactivity, and create new contexts. Teacher's directive speech acts can showability master in subject matter, the ability to delivery subject matter, and ability tointeraction. The results of this research can be used as a reference in linguistic research and interaction in teaching and learning activities.